KEEFEKTIFAN MEDIA PEMBELAJARAN INTERAKTIF CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 2 BRINGINSARI KABUPATEN KENDAL - Khoirunnisa, Elvina; Khusnul Fajriyah; Diana Endah Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted due to the usage of learning media has not been optimized. The usage of interactive media in the learning process at SDN 2 Bringinsari is still limited, which ended in low student engagement during lessons. Furthermore, student learning outcomes from daily assessments and examinations indicate are uncertain. However, the research question explored in this study is: How effective is the use of Canva-based interactive learning media in improving the IPAS learning outcomes of fifth-grade students at SDN 2 Bringinsari, Kendal? The purpose of this research is to determine the effectiveness of Canva interactive learning media in improving the IPAS learning outcomes of fifth-grade students at SDN 2 Bringinsari, Kendal. This study is a quantitative research using a pre-experimental quantitative method in the form of a One Group Pretest-Posttest Design. The population in this study consists of all fifth-grade students at SDN 2 Bringinsari, Kendal, totaling 23 students. Based on the research conducted, the data obtained showed that the average pretest score was 53.48, and the average posttest score was 85.43. The results of the paired sample t-test analysis for pretest and posttest scores showed a significance value (2-tailed) of 0.00 < 0,05, indicating a significant difference between pretest and posttest learning outcomes. The N-Gain value obtained was 68.71%, which falls into the